Coach yourself! : increase awareness, change behavior, and thrive - Bowring, Antonia (John Wiley & Sons, Inc., 2024)
"In the most basic (and driest) terms, executive coaching is a regular one-on-one development process designed to produce positive changes in business behavior in a limited time frame." Building from there, when I am hired as an executive coach, I serve as a professional reframer, cheerleader, sounding board, and accountability partner to my client. I help you develop awareness about yourself, help you unearth your challenges, and create actionable goals related to them, and then hold you accountable for achieving those goals. And the ideal result is an improved situation where you thrive (and if you lead a team, it will thrive, too)"--